1967
DOI: 10.1113/jphysiol.1967.sp008131
|View full text |Cite
|
Sign up to set email alerts
|

The significance of adenosine cyclic 3′,5′‐monophosphate for the contraction of smooth muscle

Abstract: SUMMARY1. The influence of adenosine cyclic 3',5'-monophosphate (3',5'-AMP) and of drugs believed to increase or decrease its concentration in the tissues has been determined on the response of vascular and uterine smooth muscles to catecholamines. Generally, drugs believed to increase tissue content of 3',5'-AMP potentiated the responses and those believed to decrease it depressed them.2. The cardiovascular responses of dogs (with major vessels occluded in the chest) to carotid occlusion were potentiated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

1969
1969
1982
1982

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Von Euler and Lishajko (196B) found that the ATP-dependent noradrenaline uptake into storage granules isolated from rat brain could be blocked by both a-and s-adrenergic blocking agents. increase in cyclic-AMP levels associated with a-receptor activation (Bartelstone et ~., 1967;Jarrott, 1972) are in conflict with this pro-…”
Section: General Introductionmentioning
confidence: 99%
“…Von Euler and Lishajko (196B) found that the ATP-dependent noradrenaline uptake into storage granules isolated from rat brain could be blocked by both a-and s-adrenergic blocking agents. increase in cyclic-AMP levels associated with a-receptor activation (Bartelstone et ~., 1967;Jarrott, 1972) are in conflict with this pro-…”
Section: General Introductionmentioning
confidence: 99%
“…The studies of Bartelstone & Nasmyth (1963), and of Bartelstone, Nasmyth & Telford (1967), indicated that vasoconstrictors increased the level of cyclic AMP although Robison & Sutherland (1970) claimed the converse to be the case, and Triner, Vulliemoz, Schwartz & Nahas (1970) and Volicier & Hynie (1971) showed that vasodilatation was associated with an accumulation of cyclic AMP.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible, therefore, that thyroxine potentiates the stimulant effects of (+)-amphetamine and caffeine indirectly by causing accumulation of cyclic AMP. Bartelstone, Nasmyth & Telford (1967) using smooth muscle have provided evidence that drugs which increase the tissue levels of cyclic AMP also increase responses to sympathomimetic amines, and that the reverse is also true.…”
Section: Discussionmentioning
confidence: 99%